(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This research entitled “The role of KH. Abdul Wahid Hasyim In Indonesia Administration (1945-1953)”. The research background addressed KH. Abdul Wahid Hasyim figure, who was the main pioneer in the Religious Ministry during the Unitary State of the Republic of Indonesia. During the Japanese occupation, the Religious Ministry called Shumubu, which was the embryo of the present Religious Ministry. As before independence took place, KH. Abdul Wahid Hasyim has been heavily involved in several movement organizations fighting against the occupation in Indonesia. Namely Nahdlatul Ulama (NU), in Majelis Islam A’la Indonesia (MIAI), and also within the Indonesian Muslim Shura Council (Masyumi) organization. In additional KH. Abdul Wahid Hasyim was involved in BPUPKI, the Sembilan Committee and PPKI who supported the emerge and the state of Indonesia. After entering the independence period, KH. Abdul Wahid Hasyim participated in several cabinets and his position once served as a State Minister, Religious Minister of the Republic of Indonesia, and as Religious Minister the Unitary State of the Republic of Indonesia.